2022
DOI: 10.22146/ijc.72852
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Carbon Steel Corrosion by Some New Organic 2-Hydroselenoacetamide Derivatives in HCl Medium

Abstract: This study aims to prepare 2-hydroselenoacetamide derivatives (5-8) to use some of these compounds as corrosion inhibition for carbon steel in 1 M HCl. The compound C10H10NO2Cl 1 was prepared by reacting between p-aminoacetophenone with chloroacetyl chloride, and then reacted 1 with substituted benzaldehyde to obtain the corresponding derivatives as C17H13N2O4Cl 2, C18H16NO4Cl 3 and C19H18NO4Cl 4. The last step in this study was conducted to obtain the organic hydroselenoacetamide such as C10H11NO2Se 5, C17H14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Morpholine and thiomorpholine are organic heterocyclic compounds which have several practical applications as they are the most favorable organic solvent due to their low cost and can be considered good bases [17]. A large number of heterocyclic bases, such as thiomorpholine and their derivatives, have been reported [18] due to their thermal stability and bioinorganic applications such as antimalarial and antioxidant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Morpholine and thiomorpholine are organic heterocyclic compounds which have several practical applications as they are the most favorable organic solvent due to their low cost and can be considered good bases [17]. A large number of heterocyclic bases, such as thiomorpholine and their derivatives, have been reported [18] due to their thermal stability and bioinorganic applications such as antimalarial and antioxidant.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction was stirred at room temperature for 2 h, filtered, and then the excess solvent was removed under a vacuum. To the filtrate, 30 mL of distilled water was added, and then the resulting solid was filtered, dried, and crystallized from ethanol/ water (ratio 80:20) mixture [18][19] (see Scheme 1).…”
Section: General Procedures For the Synthesis Of Compound (4)mentioning
confidence: 99%
“…The inhibitory efficiency (%IE) from the polarization investigation was computed using Eq. (1) [35][36];…”
Section: Corrosion Investigation Of Carbon Steelmentioning
confidence: 99%
“…( 2) [37][38] and demonstrated that all values are less than 85 mV. Hence, the inhibitor can be classified as an inhibitor mixture from cathodic or anodic inhibitors [35]. corr corr,without inhibitor corr,with inhibitor…”
Section: Potentiodynamic Polarizationmentioning
confidence: 99%